Prevalence of Selected Bacterial Infections Associated with the Use of Animal Waste in Louisiana - Hill, Dagne D. (Molecular Diversity Preservation International (MDPI), 2005)
Human health is a major concern when considering the disposal of large quantities of animal waste. Health concerns could arise from exposure to pathogens and excess nitrogen associated with this form of pollution. The objective was to collect and analyze health data related to selected bacterial infections associated with the use of animal waste in Louisiana. An analysis of adverse health effects has been conducted based on the incidence/prevalence rates of campylobacteriosis, E. coli O157:H7 infection, salmonellosis and shigellosis. The number of reported cases increased during the summer months. Analysis of health data showed that reported disease cases of E. coli O157:H7 were highest among Caucasian infants in the 0–4 year old age category and in Caucasian children in the 5–9 year old age category. Fatalities resulting from salmonellosis are low and increases sharply with age. The number of reported cases of shigellosis was found to be higher in African American males and females than in Caucasians. The high rate of identification in the younger population may result from the prompt seeking of medical care, as well as the frequent ordering of stool examination when symptoms become evident among this group of the population. The association with increasing age and fatality due to salmonellosis could be attributed to declining health and weaker immune systems often found in the older population. It is concluded that both animal waste and non-point source pollution may have a significant impact on human health.